2009
DOI: 10.1007/s00381-009-0985-5
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic and neuroprotective effects of mycophenolate mofetil after acute spinal cord injury in young rats

Abstract: Our results showed that the administration of mycophenolate mofetil on traumatic spinal cord injury decreases apoptosis and improves neurologic recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The observed neuroprotective effect of mycophenolate could be partially attributed to its anti-oxidant activity, as mycophenolate treatment at doses of 100 and 200 mg/kg ameliorated the raised NO activity after 24 h of ischemia (Bilginer et al, 2009). Our results demonstrated that cephalexin, mycophenolate, and atorvastatin reduced the expression of proinflammatory cytokines and oxidative stress-related factors like TNF-α, GFAP, and COX-2.…”
Section: Discussionsupporting
confidence: 52%
“…The observed neuroprotective effect of mycophenolate could be partially attributed to its anti-oxidant activity, as mycophenolate treatment at doses of 100 and 200 mg/kg ameliorated the raised NO activity after 24 h of ischemia (Bilginer et al, 2009). Our results demonstrated that cephalexin, mycophenolate, and atorvastatin reduced the expression of proinflammatory cytokines and oxidative stress-related factors like TNF-α, GFAP, and COX-2.…”
Section: Discussionsupporting
confidence: 52%
“…Weight-drop model was performed for SCI. [4,20,21] The animals were subjected to an impact of 50 g/cm to the dorsal surface of the spinal cord. The force was applied via a stainless steel rod (3 mm diameter tip, weight 5 g) that was rounded at the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Several chemicals, ranging from immunosuppressive to anti-inflammatory agents, have been studied as therapeutic agents. [ 11 , 12 ] Methylprednisolone, a strong anti-inflammatory agent that was once thought to be effective and recommended in guidelines, was later found to be ineffective in subsequent studies. Considering the severe complications associated with high-dose steroids, their use has been widely abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…This activation results in an excessive release of Ca 2+ under pathological conditions, which, in turn, may progress to cellular death. [ 12 ] The extent of axonal damage has been shown to be limited by chelating intracellular Ca 2+ . [ 13 ] It is thought that the endoplasmic reticulum (ER) is the source of intracellular Ca 2+ during injury.…”
Section: Discussionmentioning
confidence: 99%